Find “gof” and “fog”where:
\[f(x) = x - 2,\,g(x) = {x^2} + 3x + 1\]?
Answer
Verified
409.8k+ views
Hint: Here the given question is to find the value of “gof” and “fog” for the given value of the functions, here we know that to obtain the “fog” or “gof”, we need to understand the meaning of “fog” and “gof”, here “fog” means that g(x) function is inside the f(x) function and value of g(x) will be replaced on place of “x” in the “f(x)” function, and respectively for the “gof” also.
Complete step-by-step solution:
Here the given question is to find the value for the given functions, here the property of the “gof” and “fog” is to be used, we already know the meaning of both the functions, now on solving for the values of the functions we get:
First of all dealing with “gof” we get:
\[\Rightarrow gof = {(x - 2)^2} + 3(x - 2) + 1 \\
\Rightarrow gof = {x^2} - 4x + 4 + 3x - 6 + 1 \\
\Rightarrow gof = {x^2} - x - 1 \]
Now solving for “fog” we get:
\[ \Rightarrow fog = ({x^2} + 3x + 1) - 2 \\
\Rightarrow fog = {x^2} + 3x + 1 - 2 = {x^2} + 3x - 1 \]
Here we get the values for the functions.
Note: Here the given question is to solve for the function “fog and gof”, here we can not find the value without getting the meaning of the terms, and as we know that these functions required to solve after putting the value of one function into other and then solve further and get the solution.
Complete step-by-step solution:
Here the given question is to find the value for the given functions, here the property of the “gof” and “fog” is to be used, we already know the meaning of both the functions, now on solving for the values of the functions we get:
First of all dealing with “gof” we get:
\[\Rightarrow gof = {(x - 2)^2} + 3(x - 2) + 1 \\
\Rightarrow gof = {x^2} - 4x + 4 + 3x - 6 + 1 \\
\Rightarrow gof = {x^2} - x - 1 \]
Now solving for “fog” we get:
\[ \Rightarrow fog = ({x^2} + 3x + 1) - 2 \\
\Rightarrow fog = {x^2} + 3x + 1 - 2 = {x^2} + 3x - 1 \]
Here we get the values for the functions.
Note: Here the given question is to solve for the function “fog and gof”, here we can not find the value without getting the meaning of the terms, and as we know that these functions required to solve after putting the value of one function into other and then solve further and get the solution.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE